Craniofacial abnormalities among patients with Edwards Syndrome - Rafael Fabiano M. Rosa; Rosana Cardoso M. Rosa; Marina Boff Lorenzen; Paulo Ricardo G. Zen; Carla Graziadio; Giorgio Adriano Paskulin (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE To determine the frequency and types of craniofacial abnormalities observed in patients with trisomy 18 or Edwards syndrome (ES). METHODS This descriptive and retrospective study of a case series included all patients diagnosed with ES in a Clinical Genetics Service of a reference hospital in Southern Brazil from 1975 to 2008. The results of the karyotypic analysis, along with clinical data, were collected from medical records. RESULTS: The sample consisted of 50 patients, of which 66% were female. The median age at first evaluation was 14 days. Regarding the karyotypes, full trisomy of chromosome 18 was the main alteration (90%). Mosaicism was observed in 10%. The main craniofacial abnormalities were: microretrognathia (76%), abnormalities of the ear helix/dysplastic ears (70%), prominent occiput (52%), posteriorly rotated (46%) and low set ears (44%), and short palpebral fissures/blepharophimosis (46%). Other uncommon - but relevant - abnormalities included: microtia (18%), orofacial clefts (12%), preauricular tags (10%), facial palsy (4%), encephalocele (4%), absence of external auditory canal (2%) and asymmetric face (2%). One patient had an initial suspicion of oculo-auriculo-vertebral spectrum (OAVS) or Goldenhar syndrome. CONCLUSIONS: Despite the literature description of a characteristic clinical presentation for ES, craniofacial alterations may be variable among these patients. The OAVS findings in this sample are noteworthy. The association of ES with OAVS has been reported once in the literature.